Diesel and Gasoline Engines - Viskup, Richard (2020)
The internal combustion engine was invented around 1790 by various scientists and engineers worldwide. Since then the engines have gone through many modifications and improvements. Today, different applications of engines form a significant technological importance in our everyday lives, leading to the evolution of our modern civilization. The invention of diesel and gasoline engines has definitely changed our lifestyles as well as shaped our priorities. The current engines serve innumerable applications in various types of transportation, in harsh environments, in construction, in diverse industries, and also as back-up power supply systems for hospitals, security departments, and other institutions. However, heavy duty or light duty engines have certain major disadvantages, which are well known to everyone. With the increasing usage of diesel and gasoline engines, and the constantly rising number of vehicles worldwide, the main concern nowadays is engine exhaust emissions. This book looks at basic phenomena related to diesel and gasoline engines, combustion, alternative fuels, exhaust emissions, and mitigations.